Irish M.P's - Heath, William, 1795-1840 (McLean, Thomas, 1829)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; O'Connell, Daniel, 1775-1847; Irish -- Caricatures and cartoons